Environmental benefits assessment of pollution reduction and Greenhouse gas emissions from urban domestic wastewater treatment in Guangdong province - Wang Simiao; Chen Deye; Wang Zixiong; Fan Yuxin; Yan Chao; Wang Tianxiang (Renmin Zhujiang)
Although urban domestic sewage treatment reduces pollutant emissions, the greenhouse gas emissions generated during this period also force us to re-evaluate the carbon-pollution synergy environmental benefits. Based on the IPCC inventory method and the full life cycle method, this paper constructs a carbon-pollution accounting model for urban domestic sewage treatment and comprehensively evaluates the pollution reduction benefits and greenhouse gas emissions of urban domestic sewage treatment in Guangdong Province. The results show that over the past 20 years, the urban sewage treatment rate in Guangdong Province has increased by 3.22 times, and the reduction in COD, total nitrogen, and total phosphorus has increased nearly tenfold. This has effectively reduced the environmental pollution load, contributing to the improvement of the water environment in Guangdong Province. However, GHG emissions from sewage treatment have also increased fivefold, becoming a significant source of GHG emissions. Additionally, the intensity of GHG emissions has decreased by about 50%, and the indirect GHG reduction benefits from pollutant reduction have increased by about 1.8 times. These findings imply that with the improvement of sewage treatment facilities, urban domestic sewage treatment can yield more environmental benefits. It is recommended to enhance the use of clean energy and carbon recovery to improve the synergistic control capability of GHG and pollution emissions in the future.